Molecular Structures and Biochemical Physiology of the Proteins Involved in Chemical Communications in Some Insect Species - Ender Büyükgüzel (De Gruyter, 2006)
The olfactory systems of terrestial animals are designed to trap and sample volatile hydrophobic molecules. Some of these molecules are odorants, such as volatile plant compounds and pheromonesemitted from the other organisms. Insect antennae have a primary function of detecting odors including sex pheromones and plant volatiles. In moths, the organs devoted to olfactory perception have been identified in antennae as the sensilla trichoid and basiconic, the former being tuned to the perception of pheromones. The hydrophobic semiochemicals are solublized by odorant-binding proteins and transported through an aqueous environment (sensillar lymph) to the olfactory receptors, where the signal transduction starts. These proteins, subdivided into pheromone-binding proteins and general odorant-binding proteins, all have a hallmark of six conserved cysteine residues forming three disulfide bridges which are essential for the rigidity of their three-dimensional structures. Pheromones are naturally occuring odorless chemical messenger compounds found in all insects, animals, and humans. They could attract male insectsfrom a long distance exceeding kilometers. Pheromone-binding proteins are small helical proteins (13-17 kDa) present in several sensory organs from moth and other insect species. Odorant-binding proteins are small (15 kDa) soluble proteins, very concentrated in the lymph of chemosensory sensilla. A third class of small proteins has been identified in several sensorial organs from a number of insect orders. They have been separated into a group of chemosensory proteins, characterized by four cystein residues and with low sequence similarity to odorant-binding proteins. They are involved in chemoperception (olfaction and taste) and to play a role in chemical transport from air or water to chemosensitive receptors.